Sistem Pendukung Keputusan Pemilihan Rumah Kontrakan Menggunakan Metode Topsis (Technique For Orders Preference By Similarity To Ideal Solution) - Salahudin Robo; Jenifer Laura Patrisyah Rumpaisum; Friden Elefri Neno; Ajeng Kalista Rahma; Gergorius Kopong Pati; Damar Suryo Sasono (TIN: Terapan Informatika Nusantara, 2023)
Technological development is progress that occurs in the field of knowledge and technology that affects human life. Technology continues to develop and affect various aspects of human life such as business, education, health, and others. The development of digital technology, especially property technology (proptech), continues to expand into businesses and various residential and property business services. This application will continue along with technological developments and people's needs and lifestyles that continue to change. A rented house is a house that is rented for a specified time (for 1 year, 2 years, etc.) However, the reason not to buy a house or apartment is often due to costs and making rented houses an alternative option for the community. With all our preferences, choosing a rental house is not easy. because it is difficult to find information about the accuracy of searching for rented houses that match the criteria. In general, an explanation of the data collection techniques used to support the flow of research on the topsis method for selecting rented houses is interview, observation, and library research. This study uses the TOPSIS method for calculations. Thus, the purpose of this study is to propose a decision support system for selecting rental housing with various criteria. To achieve this goal, this study will use the topsis method